2011
DOI: 10.1097/nrl.0b013e3181e530a3
|View full text |Cite
|
Sign up to set email alerts
|

Pontocerebellar Angle Aspergillosis

Abstract: In immunocompromised patients, the coexistence of an infectious lesion with involvement of contiguous vessels and consequent ischemic infarction should raise the suspicion of aspergillosis, even in unusual locations such as the pontocerebellar angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Besides, one female patient with ALL underwent T11–L1 laminectomy and ultrasound-guided aspiration for her intramedullary and extra medullary abscesses [ 28 ]. The main surgical finding was a vascularized thick capsule (soft capsule) containing a necrotic purulent component, pinkish white pus or viscous fluid [ 25 , 41 , 42 ]. In one patient, after five weeks of DAMB use, the patient’s symptoms worsened; therefore, resection of the inferior temporal lobe abscesses and debridement of the external canal, petrous apex, and mastoid air cells were performed, which led to control of the infection and recovery of the patient [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, one female patient with ALL underwent T11–L1 laminectomy and ultrasound-guided aspiration for her intramedullary and extra medullary abscesses [ 28 ]. The main surgical finding was a vascularized thick capsule (soft capsule) containing a necrotic purulent component, pinkish white pus or viscous fluid [ 25 , 41 , 42 ]. In one patient, after five weeks of DAMB use, the patient’s symptoms worsened; therefore, resection of the inferior temporal lobe abscesses and debridement of the external canal, petrous apex, and mastoid air cells were performed, which led to control of the infection and recovery of the patient [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given that the clinical signs of CNS aspergillosis are usually nonspecific and similar to other diseases, differential diagnosis such as lung cancer, cerebral infection or abscesses such as listeriosis, cryptococcal and tuberculous meningitis, metastatic disease and cerebral malignancy should be considered when imaging modalities are used for diagnosis in patients [ 39 ]. Noteworthy, the MRI appearance of CNS aspergillosis depends on different factors such as the timing of neuroradiologic assessment, immunologic status of the patient, and the characteristics of the fungus [ 42 ]. However, our results showed that on conventional MRI sequences in patients with leukemia, CNS aspergillosis appears as ring-enhancing lesions, with perifocal edema on MRI.…”
Section: Discussionmentioning
confidence: 99%